PERAN PENGAWAS TK DALAM MENJALANKAN FUNGSI SUPERVISI DI TK SE- KECAMATAN PANGEAN - Eka Deni (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2016)
The research carried out aims to understand the role of kindergarten supervisors in carrying out the supervision function in Pangean District, Kuantan Singing Regency. This research was conducted through qualitative methods and using observation and interview data collection techniques. This study uses qualitative data analysis techniques. Based on the research results, the following results are obtained; the role of supervisors is very important in advancing the school and the institution it supervises, so between supervisors and principals occurs because of the existence of work relationships and forming perceptions between them. The implications of the above conditions of educators and components and services in kindergartens to the target have not been able to run in accordance with the provisions of early childhood education services. This is because the communication process between supervisors and school principals is hampered, as in one of the roles of supervision and reporting in the field of curriculum, to date the curriculum is still being socialized to be standardized. The supervision process is an important indicator in the tasks carried out by supervisors in the UPTD because it shows a clear process in changing school conditions in terms of administration and competence in a professional manner.